(untitled) (Cadernos de Sociomuseologia, 2024)
In the 1960s, in the midst of the Cold War, the National Campaign for Regional Museums aimed to encourage the opening of regional museums of modern art throughout Brazil, promoting the decentralization of art museums in the country, offering other regions museums of excellence, powerful equipment for the dissemination and dynamic expression of local art, which would be intentionally in dialogue with the national and international artistic and museological scene, with these regional museums being managed by civil society, enjoying full autonomy from the government. The leaders of the Campaign were linked to the modernist movement in São Paulo, which at that time became a national symbol, as well as to international economic and technical-cultural capital, represented respectively by Rockefeller, ICOM and UNESCO and some assumptions of the New Museology. This network of relationships and the circulation of ideas, albeit with different objectives, resulted in the foundation of the São Paulo Museum of Art (1947), an institution that technically subsidized the National Campaign for Regional Museums, and the São Paulo Museum of Modern Art (1948), an institution that organized the first editions of the São Paulo International Art Biennial, maximizing the prestige and symbolic power of the Campaign. In this way, just like the institutions that subsidized the Campaign, the regional museums of Olinda, Campina Grande and Feira de Santana were also caught between modern art and contemporary art, not only in the constitution of their collection, but mainly in their consolidation and regional artistic promotion. This article, using the dialogic method, aims to explore the relational dynamics of implementation and dialogue between the international, national and regional scenarios, which were intended to promote local social development, with the implementation and operation of regional museums as the architect, promoted and encouraged by the National Campaign for Regional Museums, a project fostered from São Paulo, with the intense and preponderant legitimizing participation of the São Paulo Museum of Art (MASP). Keywords: Regional Museums; Modern Art; New School; New Museology; Regional Development